EV-out or EV-in: Tackling cell-to-cell communication within the tumor microenvironment to enhance anti-tumor efficacy using extracellular vesicle-based therapeutic strategies - Wararat Chiangjong; Somchai Chutipongtanate (Elsevier, 2022)
Tumor development is influenced by cell interactions within the tumor microenvironment (TME). Extracellular vesicles (EVs) released from tumor cells mediate critical signals that communicate with their TME to modulate tumor progression. These EVs can result in resistance to chemotherapy or immunotherapy during cancer treatment. Studies related to tumor-derived EV biogenesis and components have led to new strategies to enhance tumor sensitivity to standard treatments by blocking or neutralizing EV formation. Furthermore, engineered EVs expressing specific ligands and receptors have been investigated for targeted tumor delivery of therapeutic agents, improving treatment efficacy, and mitigating adverse effects. In addition, EVs have been modified to function as tumor vaccines to promote cancer immunity.